2003
DOI: 10.5713/ajas.2003.983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementary Feeding of Concentrate on Nutrient Utilization and Production Performance of Ewes Grazing on Community Rangeland during Late Gestation and Early Lactation

Abstract: Malpura and Kheri ewes (76) in their late gestation, weighing 34.40±0.95 kg were randomly selected and divided into 4 groups of 19 each (G1, G2, G3 and G4). Ewes in all the groups were grazed on natural rangeland from 07.00 h to 18.00 h. Ewes in G1were maintained on sole grazing while ewes in G2, G3 and G4, in addition to grazing received concentrate mixture at the rate of 1% of their body weight during late gestation, early lactation and entire last quarter of pregnancy to early quarter of lactation, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 9 publications
16
12
0
Order By: Relevance
“…As regards birth weight, the results observed in this study were similar to those reported by Chaturvedi et al (2006), who did not find an effect of flushing on Malpura ewes on the birth weight of the lamb; and contrary to those found by Chaturvedi et al (2003), who, studying the effect of supplementation on performance and production of Malpura and Kheri ewes on natural pasture, recorded higher birth weights in lambs from ewes supplemented during the end of gestation and beginning of lactation due to the low pasture quality. The average prolificacy of 1.25 was similar to the 1.30 described by Veloso (2008), who evaluated the productive and reproductive performance of ewes subjected to different flushing systems.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As regards birth weight, the results observed in this study were similar to those reported by Chaturvedi et al (2006), who did not find an effect of flushing on Malpura ewes on the birth weight of the lamb; and contrary to those found by Chaturvedi et al (2003), who, studying the effect of supplementation on performance and production of Malpura and Kheri ewes on natural pasture, recorded higher birth weights in lambs from ewes supplemented during the end of gestation and beginning of lactation due to the low pasture quality. The average prolificacy of 1.25 was similar to the 1.30 described by Veloso (2008), who evaluated the productive and reproductive performance of ewes subjected to different flushing systems.…”
Section: Resultssupporting
confidence: 82%
“…The greater ADG of supplemented ewes might have resulted from their higher nutrient intake. The results of this study are similar to those reported by Mori et al (2006) and Veloso (2008), who, evaluating the reproductive performance of ewes at the beginning and during the breeding season, observed higher ADG in the supplemented ones; and by Chaturvedi et al (2003), who studied the effect of supplementation on performance and production of Malpura and Kheri ewes on a natural pasture during the end of gestation and in early lactation, and observed a higher ADG in the supplemented animals.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This difference may be again due to extra concentrate supplementation during advance period of gestation. Milk yield was also more in ewes supplemented additional concentrate in late gestation period and increase was upto 200 g/day (Chaturvedi et al, 2010). Further it was supported by Sibanda et al (1997) that amount of feed offered in lactation had a positive effect upon milk yield and there was an increasing trend for milk yields to prepartum dietary intake.…”
Section: Resultssupporting
confidence: 50%
“…Gain in BW was also observed in T1 group kids than T0 group however the difference was non-significant. Chaturvedi et al (2010) …”
Section: Page88mentioning
confidence: 99%